Female Executives and Corporate Performance: Evidence from China - Dong, Yuhan (2020)
There is much literature that looks to examine the influence of female executives on corporate performance. Glass ceiling theory, agency theory and stakeholder theory helps to understand the factors that influence the existence of female executives. Empirical evidence shows that glass ceiling and women's self-consideration can hinder women's promotion, while women's unique perspectives and abilities attract companies to promote them to senior management. Moreover, female executives are more democratic and risk-averse. This paper uses empirical evidence to discuss the relationship between female executives and corporate performance. It uses data of 1,395 listed companies in China from the year 2015 to 2019 as a research sample. An empirical analysis on the relationship between female executives and corporate performance is provided, as well as on the mediating effect of female executives' education level. Additionally, this paper explores the relationship of female executives under different corporate ownership structures on corporate performance. The results of this paper find that female executives are more represented in the service and emerging industries. It also finds that there is a significant positive relationship between female executives and corporate performance, and between female executive education levels and corporate performance. Finally, this paper finds that the influence of female directors on corporate performance is higher significant in non-state-owned companies than that in state-owned companies. This paper expands on earlier research in the literature and adds new empirical evidence. Also, this paper provides a unique management perspective for Chinese boards of directors and offers useful guidance for Chinese regulators on the issue.